A case report: Atropine drops induced psychosis after sublingual administration for sialorrhea treatment in a stroke patient - Mohd Azhar, Nur Syuhada; Abu Hassan, Salmah Anim (Hospital Raja Permaisuri Bainun, 2022)
INTRODUCTION Sialorrhea also known as drooling is defined as excessive saliva in the mouth or hypersalivation. Sialorrhea may affect physical, mental, self-esteem and social due to social stigma among families and friends. Advanced complications might also develop such as aspiration pneumonia. OBJECTIVES To know the research data regarding the use of sublingual atropine to manage sialorrhea and the side effects. METHODOLOGY Observation case study of 61 years old man with posterior circulation infarction was given ophthalmic atropine 1% via sublingual route for management of his sialorrhea. The patient was initiated with sublingual atropine 1%, 1mg (2 drops) 6 hours apart. RESULTS Approximately 6 hours after the first dose, the patient exhibited dry mouth and symptoms of anticholinergic delirium-excessive talking, paranoid delusions, hallucinations and insomnia. Other signs of anticholinergic toxidrome such excessive tachycardia, mydriasis and urinary retention were absent. After 16 hours of atropine initiation, the patient was already alert, orientated, but oral examination showed complete xerostomia. CONCLUSION Physicians treating sialorrhea with anticholinergics should be aware regarding the risk of atropine delirium and anticholinergic toxidrome. Considerations to use other anticholinergics such as glycopyrrolate that has poor blood brain barrier permeability should be considered.